Gender Power Relations in Putin's Speech on The Russian Invasion of Ukraine - Jonathan Imanuel Misman (Publikasi Indonesia, 2025)
The Russian invasion of Ukraine that has occurred since February 24, 2022 has shown Russian masculinity in dominating Ukraine. The language construction delivered by Putin in his speech narratives illustrates unequal gender power relations. The assumption of Russia as a man who came to protect Ukraine from Western influence justifies the violence and war they are carrying out. The patriarchal and machismo social system in Russia is also a source of violence as well as legitimizing Russia's actions. The image of Putin as a macho leader cannot be separated from the narrative he uses in his speech. Therefore, this paper aims to answer the question of how feminism reads Putin's language construction in military operations in Ukraine. To answer this question, the author uses a feminist poststructuralist approach. Through this approach, it can be understood that the discourse in Putin's speech narrative has constructed a language that gives meaning to the concept of gender based on Russian traditional values. This meaning influences the perceptions and actions of Russian society in the conflict in Ukraine.